Modeling a modern tram system integrated with a road traffic simulation. (January 2018) - Zhao, Xing; Li, Yan; Xu, Shanshan; Zhai, Hui
For the purpose of presenting running processes, assessing the efficiencies of operation plans of modern trams and corresponding adjustments of road traffic signal timing, and reflecting the influence of interactions between tram signals and road traffic signals to the regional transport network, this paper formulates a microscopic model for the modern tram system integrated with a road traffic simulation which contains six modules: the passenger module, the tram vehicle module, the tram equipment module, the road traffic module, the interaction module, and the performance module. Then, validation of the model is presented by comparing the travel time of field observations and simulation results of the proposed model, and statistical testing of the average passenger waiting time and number of waiting passengers. Overall, two applications are developed to illustrate the model capabilities and application value. The first example compares average queuing lengths of urban road traffic at an intersection under different departing intervals of trams; the second one designs the plans of traffic signal coordination control and tram running processes to realize a two-directional green wave for trams.